Perfil de sub-proyecto regional promocion al consumo del frejol, bases preliminares: Bolivia - Ecuador - Peru - Bernal de Amory, Z.; Peralta, E.; Arriola, V.O.; Sanz M., M.E.; Vásquez, J.; Córdoba, P.; Castillo, R.; Castro, P.; Duenas C., R. (International Center for Tropical Agriculture, 1991)
The general objective of the sub-project is to introduce beans as a component in the daily diet within the low-income population in Bolivia, Ecuador, and Peru. Its specific objective is to identify the main variables which currently determine the low bean consumption in the Andean zone population, enabling the bases for implementing consumption promotion programs to be established. In Bolivia, research will be conducted in the tropical areas of Santa Cruz, mainly in the marginal areas of the capital city and in regional colonization zones. In Ecuador, operations will be located in strategic sites of the Sierra and Coastal regions. In Peru, research will be conducted in the provinces of Urubamba, Calca, Anta, and Cuzco (Ucchullo, Puquin, and Ollanta districts), in the Andean Sierra. Surveys and interviews will be carried out on bean consumption patterns and culinary technology within the target groups involved. The 2-step stratified statistical sampling method will be used for the study. The sub-project will require US$3000 from PROFRIZA during 1991 and will cover a 5 mo. period (from Aug. to Dec.). Total duration will be 3 yr (from the 2nd semester 1991 to the 1st semester 1993). Once the variables are identified, actions will be drawn to encourage regional bean consumption which is expected to increase among the groups involved up to 1000, 2000, and 3000 g/capita in the 1st, 2nd, and 3rd yr, resp. (AS-CIAT)